En omstridt Grundtvig-salme og dens forstadier - Jensen, Th Borup (Grundtvig-studier, 1970)
Thorkild Borup Jensen, “A Much-Debated Grundtvig Hymn and its Preliminary Stages” In the first part of this study it is shown, by means of an analysis of structure, style, and content, that the hymn »O Christelighed« (Oh Christianity) ( 1853) meets the demands that Grundtvig himself made on the genre from the mid 1820’s onwards: The hymn should “express the living feeling that we have already passed from death to life, have found eternal life in the love of God, and have drunk of the chalice of his blessedness”. The hymn “O Christelighed” is partly a visionary image of the absolute, complete, and unqualified state of blessedness (st. 1- 3 ), partly a richly symbolic account of its causes, both those originating in human nature (Tro og Haab (faith and hope) st. 4- 5 ), and those originating in divine nature (Kiærlighed (charity), st. 6- 7 ). The entire hymn is pervaded by a sense of ecstatic enthusiasm inspired by the experience of the Promised Land of Christianity here and now, and also by the certainty that the experience will continue unbroken.In the last part of the study the two earlier versions of the hymn are taken into account as well, viz. “ Jeg kjender et Land” (I know a land) ( 1824) and “O dejlige Land” (Oh blessed land) ( 1832). From the three variants it is shown how Grundtvig as an artist was perpetually inspired by the baroque hymn writer Kingo—and how as a Christian preacher he dissociates himself from Kingo with increasing consistency: Conceptually, and artistically, the version of 1824 comes closest to Kingo’s hymn “ Far, Verden, far vel” (a farewell to the world); in the version of 1832 there are still many Kingo reminiscences, but in the version of 1853 these are totally eradicated.